Traditional Parang Designs And Carvings In Borneo - Muhyiddin, Mohammed; Saiful Bahari, Hj Mohd Yusoff; Mohamad, Fairuz Ali (IJIDeCS, 2018)
The ancient inherited art of carving skills on the traditional machete or parang (in Malay Language) has been well preserved until today. In order to produce a high quality design and carving of a parang, it requires a creative and highly skilled blacksmith. Patience is the utmost virtue that the blacksmith needs to possess in order to ensure the completed engraving of the parang is accurate. Nadzarul Amir Zainal Alam (2008) said that a thorough wood selection process is emphasized in order to produce a beautiful and high quality hilt of the parang. Based on a research by Mohd Nurazwan Augustine (2012), the carving technique of the parang is divided into two types namely carved carving and fine carving. The objectives of this study are to study on the carvings design for parang in Borneo, to make a comparison of carved motifs on the hilts and sheath of parang and to generate empirical data on the design of traditional parang. The results can also be used as guidelines to improve the local arts and culture of the local community and hence become an important product for commercialization.